Propuesta de un programa radial dirigido a los emprendedores principiantes del cantón Huaquillas de la provincia de El Oro - Sarango Bazurto, Sammy Shaden (2024)
This research work proposes the development of a specialized radio program for early entrepreneurs of the Huaquillas canton, in the province of El Oro, Ecuador. The main objective is: To implement this specialized radio program on entrepreneurship to contribute to the positioning of early entrepreneurs from the Huaquillas canton during the year 2024. Where new entrepreneurs who have started their activities in the last year will be supported. This research was carried out with a mixed approach methodology, applying the inductive method to collect and analyze qualitative and quantitative data. In the quantitative data that was obtained, the sample was made up of 22 participants, who were early entrepreneurs. In the qualitative data, information was obtained using in-depth interviews with ten developed entrepreneurs, 6 radio experts and three entrepreneurship experts, moreover, a focus group was conducted with 6 participants who were early entrepreneurs. The categories for this study focused on public interest, current media coverage, program characteristics, such as content. The results showed that 91% of entrepreneurs use social networks as a means of promoting their business, and 45% of beginning entrepreneurs told us that they would definitely participate in a radio program specializing in entrepreneurship. On the other hand, radio experts, entrepreneurs, and developed entrepreneurs agreed on the most important things, as well as the most outstanding things, that should be implemented in a program specializing in entrepreneurship. Keywords: Radio program, entrepreneurs, Huaquillas.